Community Empowerment through Household Organic Waste Management Using Black Soldier Fly (BSF) Maggots in PRA Tegalrejo, Yogyakarta - pratiwi, Ambar; Irsalinda, Nursyiva; Luqmana, Ichsan; Eryati, Eri; Camida TA, Sutan Nur; Sirly, Churin S; Zulfikar, Zakhrul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Household organic waste management in densely populated areas such as Tegalrejo, Yogyakarta, poses a significant challenge that impacts both environmental quality and public health. This community service program aimed to enhance the knowledge and skills of local residents—particularly members of the PRA Tegalrejo women's group—in utilizing Black Soldier Fly (BSF) larvae, or maggots, as biological agents for organic waste decomposition. The training was conducted through educational sessions, live demonstrations on maggot utilization, and interactive discussions. The results showed a 14.73% increase in participants’ understanding, based on pretest and posttest scores. Participants not only gained knowledge about the decomposition process using maggots, but also recognized the potential of maggot farming as a source of animal feed and local economic opportunity. This program demonstrates that hands-on, eco-friendly education can effectively encourage community participation in waste management while simultaneously strengthening environmental resilience and household socio-economic sustainability.